Mental Health Program Effects on Public Service Delivery and Good Governance Among Local Institutions of Higher Learning in the Philippines - Ebro, Eric (Journal of Governance and Administrative Reform, 2025)
Abstract Good governance, which is achieved through the delivery of high-quality public services, is closely linked to the quality of the government’s bureaucracy. This study examined the perceptions and experiences of school leaders and personnel regarding the impact of mental health programs on public service delivery and good governance. The research adopted a qualitative descriptive design. Qualitative data were gathered through validated interview and analyzed using a content analysis approach. The study included 21 school leaders and 19 personnel as participants. The findings suggest that mental health programs contribute significantly to enhancing workplace efficiency, strengthening public service, promoting worker well-being, improving decision-making, increasing work productivity, and fostering a positive work culture. These factors collectively support the realization of good governance. The research outcomes provide valuable insights that could inform local policymaking, particularly in improving public service delivery and promoting good governance among local higher education institutions through the implementation of effective mental health programs.  Keywords: Mental health program; public service delivery; good governance.     Abstrak Pemerintahan yang baik, yang tercapai melalui penyediaan layanan publik berkualitas tinggi, sangat terkait dengan kualitas birokrasi pemerintah. Penelitian ini mengkaji persepsi dan pengalaman pemimpin sekolah serta personel mengenai dampak program kesehatan mental terhadap penyampaian layanan publik dan pemerintahan yang baik. Penelitian ini mengadopsi desain penelitian deskriptif kualitatif. Data kualitatif dikumpulkan melalui wawancara yang telah divalidasi dan dianalisis menggunakan pendekatan analisis isi. Penelitian ini melibatkan 21 pemimpin sekolah dan 19 personel sebagai peserta. Temuan penelitian menunjukkan bahwa program kesehatan mental memberikan kontribusi signifikan dalam meningkatkan efisiensi tempat kerja, memperkuat layanan publik, mempromosikan kesejahteraan pekerja, meningkatkan pengambilan keputusan, meningkatkan produktivitas kerja, dan membina budaya kerja yang positif. Faktor-faktor ini secara kolektif mendukung terwujudnya pemerintahan yang baik. Hasil penelitian ini memberikan wawasan berharga yang dapat digunakan untuk informasi bagi pembuatan kebijakan lokal, khususnya dalam meningkatkan penyampaian layanan publik dan mempromosikan pemerintahan yang baik di antara institusi pendidikan tinggi lokal melalui penerapan program kesehatan mental yang efektif. Kata kunci: Program kesehatan mental; penyampaian layanan publik; pemerintahan yang baik